Identification of a Metabolic, Transcriptomic, and Molecular Signature of Patatin‐Like Phospholipase Domain Containing 3–Mediated Acceleration of Steatohepatitis. Issue 4 (19th March 2021) - Banini, Bubu A.; Kumar, Divya P.; Cazanave, Sophie; Seneshaw, Mulugeta; Mirshahi, Faridoddin; Santhekadur, Prasanna K.; Wang, Liangsu; Guan, Hong Ping; Oseini, Abdul M.; Alonso, Cristina; Bedossa, Pierre; Koduru, Srinivas V.; et al.
Abstract : Background and Aims: The mechanisms by which the I148M mutant variant of the patatin‐like phospholipase domain‐containing 3 (PNPLA3 I148M ) drives development of nonalcoholic steatohepatitis (NASH) are not known. The aim of this study was to obtain insights on mechanisms underlying PNPLA3 I148M ‐induced acceleration of NASH. Approach and Results: Hepatocyte‐specific overexpression of empty vector (luciferase), human wild‐type PNPLA3, or PNPLA3 I148M was achieved using adeno‐associated virus 8 in a diet‐induced mouse model of nonalcoholic fatty liver disease followed by chow diet or high‐fat Western diet with ad libitum administration of sugar in drinking water (WDSW) for 8 weeks. Under WDSW, PNPLA3 I148M overexpression accelerated steatohepatitis with increased steatosis, inflammation ballooning, and fibrosis ( P < 0.001 versus other groups for all). Silencing PNPLA3 I148M after its initial overexpression abrogated these findings. PNPLA3 I148M caused 22:6n3 docosahexanoic acid depletion and increased ceramides under WDSW in addition to increasing triglycerides and diglycerides, especially enriched with unsaturated fatty acids. It also increased oxidative stress and endoplasmic reticulum stress. Increased total ceramides was associated with signature of transducer and activator of transcription 3 (STAT3) activation with downstream activation of multiple immune‐inflammatory pathways at a transcriptomic level by network analyses. Silencing PNPLA3 I148M reversed STAT3 activation. Conditioned media from HepG2 cells overexpressing PNPLA3 I148M increased procollagen mRNA expression in LX2 cells; this was abrogated by hepatocyte STAT3 inhibition. Conclusions: Under WDSW, PNPLA3 I148M overexpression promotes steatosis and NASH by metabolic reprogramming characterized by increased triglycerides and diglycerides, n3 polyunsaturated fatty acid depletion, and increased ceramides with resultant STAT3 phosphorylation and downstream inflammatory pathway activation driving increased stellate cell fibrogenic activity.